2021
DOI: 10.1016/j.xkme.2021.02.010
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seropositivity Rates in Patients and Clinical Staff in New York City Dialysis Facilities: Association With the General Population

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…plays a significant role in the spread of COVID-19 among in-center hemodialysis patients. This conclusion is supported by a different line of research that investigated the presence of SARS-CoV-2 antibodies in the general population in New York City neighborhoods and hemodialysis patients who dwelled in those areas [6]. This study showed a strong association between seropositivity rates in the general population and dialysis patients, supporting the notion that COVID-19 infection in in-center maintenance HD patients can primarily be attributed to community-acquired infection.…”
Section: Plos Onesupporting
confidence: 58%
“…plays a significant role in the spread of COVID-19 among in-center hemodialysis patients. This conclusion is supported by a different line of research that investigated the presence of SARS-CoV-2 antibodies in the general population in New York City neighborhoods and hemodialysis patients who dwelled in those areas [6]. This study showed a strong association between seropositivity rates in the general population and dialysis patients, supporting the notion that COVID-19 infection in in-center maintenance HD patients can primarily be attributed to community-acquired infection.…”
Section: Plos Onesupporting
confidence: 58%
“…The same hypothesis was evoked by Anand et al in a US nationwide comparative study which found that residents of neighborhoods with high population density presented a ten times higher risk of seropositivity compared with residents of lowest density areas [ 12 ]. Another US study showed that seroprevalence in the general and hemodialysis population are similar [ 15 ]. Since the early pandemic, epidemiological studies suggested that SARS-CoV-2 basic reproduction number (R0) increases linearly with population density [ 16 ] and this was why clusters were observed in crowded and confined spaces, mass gatherings, and populous metropolitan areas [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)10,13,14,15) Centres in India, Iran, South Africa, and Turkey have reported SARS-CoV-2 infection rates between 7 -47% amongst their dialysis patients, with fatality rates of 2 -38%. (3)(4)(5)11,12,24) While infection rates in LMICs were generally higher than in HICs, differences may reflect the community infection burden at that time rather than within centre transmission, (6,8,25,26) although outbreaks within centres have been reported globally. (6,7) Centre layout, including available side rooms for isolation, and patient factors have also been associated with the risk of infection.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%